The potential use of collaborative ESP testing implementation framework (CETIF) in addressing underlying issues in ESP curriculum and testing faced by English lecturers teaching engineering students / Norkhairi Ahmad, Ahmad Mazli Muhammad and Asiah Jamil - Ahmad, Norkhairi; Muhammad, Ahmad Mazli; Jamil, Asiah (Universiti Teknologi MARA Shah Alam, 2018)
Albeit the presence of educational quality initiatives like Outcome Based Education (OBE) and Common European Framework of Reference (CEFR) to enhance the implementation and outcome of university language courses, deep seated issues continue to leave a trail of shortcomings in the outcomes and abilities of university graduates in terms of language and communication. Detailed qualitative responses via purposive sampling elicited from experienced English lecturers teaching ESP courses to engineering students at universities in Malaysia, revealed underlying issues that stemmed from the systemic aspects of the engineering curriculum planning and execution. Issues like inaccurate course positioning in programme structure and marginalized roles of English lecturers that affect ESP courses implementation were identified via contextual analysis. Guided by the list of issues and theoretical underpinnings, a framework was proposed for mitigation efforts. The collaborative ESP testing implementation framework (CETIF) which is tied-up to language testing principles of Validity, Reliability, Impact, Practicality, and Quality management (VRIPQ) and ESP principles like specificity, authenticity and learners’ needs, embodies mitigation efforts and synergy between practitioners like English lecturers, engineering lecturers, and industry personnel. Discussion on the potential use of CETIF is put forth and the potential benefits to be yielded include enhancement of English lecturers’ professional roles, forming of positive beliefs and views and cultivation of good ESP testing practices.